Pengaruh Gaya Belajar VAK pada Penerapan Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar IPA Fisika Siswa SMP Negeri 2 Narmada Tahun Ajaran 2015/2016 - Nurmayani Nurmayani; Muhammad Zulfikar Syuaib; Jannatin Ã¢â¬ËArdhuha (Department of Physics Education, Universitas Mataram, 2016)
This ÃÂ quasi-experimental research aims at revealing (1) the effect of ÃÂ PBL learnings model on physics sciences studentÃ¢â¬â¢s learning outcomes (2) the effect of ÃÂ VAK learning styles on physics sciences studentÃ¢â¬â¢s learning outcomes (3) the interaction effects between learnings model with learning style on physics sciences studentÃ¢â¬â¢s learning outcomes. The population is all students of SMP Negeri 2 Narmada grade VIII consisting of 87 students, and 59 of which were used as samples that were chosen by purposive sampling technique. The research design used 2 x 3 factorial design and data were analysed by using two ways Anova at significant level ÃÂ± of 0.05. The results ÃÂ indicated that: (1) PBL learningÃ¢â¬â¢s model has an effect on ÃÂ the physics science studentÃ¢â¬â¢s learning outcomes as shown by a higher Fcount in comparison to Ftable (21.15 and 4.02, respectively); ÃÂ (2) learning styles has an effect on physics sciences studentÃ¢â¬â¢s learning outcomes as shown by a higher Fcount in comparison to Ftable (5.39 and 3.17, respectively); (3) an interaction effect does exist between the learning model with learning style on physics sciences studentÃ¢â¬â¢s learning outcomes up to 50.2 % ÃÂ as shown by a higher Fcount in comparison to Ftable with values of 16.13 and 3.17, respectively.